Peran Motivasi Kerja Terhadap Disiplin Kerja Aparat Kepolisian di Polsek Kelapa Lima Kota Kupang - Made Utari Anggraeni; Yeni Damayanti; Helga J. N. Ndun (Journal of Health and Behavioral Science, 2019)
Work motivation is a condition that forces or causes someone to take action consciously. Meanwhile, work discipline is a level of compliance to the existing rule and be ready to receive punishment if not following the rule. The objective of this research is to know the effect of work motivation towards work discipline for the police officers in Kelapa Lima sector police office, Kupang in 2018. This research used sampling total method of 78 samples police officer in Kelapa Lima sector police office. The bivariat test used simple linear regression test with the level of significance or alpha 0.05. Data were collected by using work motivation psychology scale and work discipline scale. The result showed work motivation on work discipline in the Police Officers in the Kelapa Lima Sector Police, Kupang in 2018 that there is a significant effect between work motivation on work discipline. These results provide information that increased work motivation will also provide improvements to work discipline.